Efficacy of chemotherapy with benznidazole in children in the indeterminate phase of Chagas' disease - Sosa-Estani, Sergio (1998)
A double-blind, randomized, clinical field trial was designed to test the efficacy and tolerance of a specific drug treatment in children in the indeterminate phase of infection by Trypanosoma cruzi. Children were treated with benznidazole at a dose of 5 mg/kg/day for 60 days or placebo and followed-up for 48 months. The treated children showed a significant decrease in geometric mean titers of antibodies against T. cruzi measured by indirect hemagglutination, indirect immunofluorescence, and ELISA. After a four year follow-up, 62% of the benznidazole- treated children and no placebo-treated child were seronegative for T. cruzi when tested by an ELISA using a T. cruzi flagellar calcium-binding protein (F29). Xenodiagnosis carried out after 48 months of follow-up was positive in 4.7% of the benznidazole-treated children and in 51.2% of the placebo-treated children. These results show the tolerance to and efficacy of benznidazole against T. cruzi in seropositive children six to 12 years of age. We used an early serologic marker of cure after treatment, consisting of a recombinant antigen implemented in a rapid, conventional serologic procedure.